Size effects in lead telluride thin films and thermoelectric properties - Olkhovskaya, S. I.; Rogacheva, E. I. (Institute of Thermoelectricity, 2013)
The influence of thickness d on thermoelectric properties (the Seebeck coefficient S, electric conductivity σ, the Hall coefficient RH, charge carrier mobility μН) of films d = 8 – 170 nm in thickness, prepared by vacuum evaporation of PbTe crystals with lead excess onto (001) KCl substrates coated with Al2O3 layer has been studied. It has been established that films with d < 75 nm possess hole conductivity, and at d > 75 nm carrier transport is determined by n-type charge carriers. The inversion of conductivity sign close to d ≈ 75 nm is attributed to a change in thermodynamic equilibrium conditions in the films as compared to crystal, as well as to material evaporation and condensation features. Oscillations on the d-dependences of the kinetic coefficients of films with p-type conductivity are attributable to quantization of the hole gas of carriers. Calculation of oscillation period Δd using a model of infinitely deep rectangular potential well is in good agreement with the experimentally determined Δd value. For n-type conductivity films the values of kinetic coefficients increase with increase in d, which points to manifestation of a classical size effect.
Keywords: thin film; classical and quantum size effect; thickness